Causal association between depression and intracranial aneurysms: a bidirectional two-sample Mendelian randomization study - Wu, Jujiang; Sun, Hao; Ma, Junqiang (Frontiers in Neurology, 2024)
Background Although observational studies have suggested a bidirectional relation between depression and intracranial aneurysms (IAs), their causal relations remain unclear. Thus we aimed to assess the causal association between depression and IAs. Methods We conducted a bidirectional two-sample Mendelian randomization (MR) study using summary-level data from publicly available genome-wide association studies of depression (n = 500,199), IAs (n = 79,429), unruptured intracranial aneurysm (uIA) (n = 74,004), and subarachnoid hemorrhage (SAH) (n = 77,074). MR analyses included the inverse-variance weighted (IVW) method as the primary analytic, plus weighted-median, simple mode, weighted mode, MR-Egger, and MR PRESSO. Results Genetically predicted depression was strongly positively related to IAs (odds ratio [OR] = 1.69, 95% confidence interval [CI] 1.19–2.39, p = 0.003), uIA (OR = 1.96, 95% CI 1.06–3.64, p = 0.032), and SAH (OR = 1.73, 95% CI 1.14–2.61, p = 0.009). Reverse MR analyses showed that while genetically predicted uIA was positively related to depression (OR = 1.02, 95% CI 1.00–1.05, p = 0.044), no causal relations were observed for either IAs or SAH for depression. Conclusion Our findings provide evidence of a causal effect of depression on IAs, uIA, and SAH. For the reverse MR analyses, we found a causal impact of uIA on depression, but no causal influence of either IAs or SAH for depression.